Laboratory-scale hydrodynamic cavitation assessment for the disinfection of filtered water in the municipality of Florencia- Caquetá - Angel Aguirre, Stefany Julieth; Agudelo Valencia, Rafael Nikolay (Ingeniería Solidaria, 2021)
Introduction: This article is the product of the research “Laboratory-scale hydrodynamic cavitation assess-ment for the disinfection of filtered water in the municipality of Florencia- Caquetá”, carried out at the University of the Amazon - Macagual Research Headquarters between 2018 and 2019. Problem: Due to the cost of chemical inputs for disinfection and the lack of trained personnel for the operation of purification systems, it is necessary to search for alternatives that require fewer chemical products and ease of operation to ensure the microbiological quality of the water supplied to the population. Objective: To evaluate, at a laboratory scale, the efficiency of a hydrodynamic cavitation reactor in terms of reducing the concentration of fecal coliforms for water disinfection in the municipality. Methodology: In order to explore the results of the proposed alternative and its statistical analysis, a type 32 factorial experimental design is used, in which the variables or factors were the initial pH of the filtered water and the diameter of the venturi throat. Results: They indicate that for a smaller diameter of the throat of the Venturi 0.00635 m (0.125 inches) and initial pH of the water of 8.5, 98.62% removal of fecal coliforms is achieved in the filtered water.Conclusion: The maximum percentage of removal of E. coli reached was 98.62%, which is why this technique should not be considered as a single treatment for water disinfection. Originality: In the present case, the evaluation of the CH for the disinfection of filtered water is carried out for a population that has difficulties with its supply of chemical inputs for water purification.Limitations: Due to its jungle location, the municipality is vulnerable to the evolution and development of tech-nological advances in regard to detailed treatments and studies in water disinfection